Exercise Counteracts Aging-Related Memory Impairment: A Potential Role for the Astrocytic Metabolic Shuttle - Tsai, Sheng-Feng; Chen, Pei-Chun; Calkins, Marcus J.; Wu, Shih-Ying; Kuo, Yu-Min (Frontiers in Aging Neuroscience, 2016)
Age-related cognitive impairment has become one of the most common health threats in many countries. The biological substrate of cognition is the interconnection of neurons to form complex information processing networks. Experience-based alterations in the activities of these information processing networks lead to neuroadaptation, which is physically represented at the cellular level as synaptic plasticity. Although synaptic plasticity is known to be affected by aging, the underlying molecular mechanisms are not well described. Astrocytes, a glial cell type that is infrequently investigated in cognitive science, have emerged as energy suppliers which are necessary for meeting the abundant energy demand resulting from glutamatergic synaptic activity. Moreover, the concerted action of an astrocyte-neuron metabolic shuttle is essential for cognitive function; whereas, energetic incoordination between astrocytes and neurons may contribute to cognitive impairment. Whether altered function of the astrocyte-neuron metabolic shuttle links aging to reduced synaptic plasticity is unexplored. However, accumulated evidence documents significant beneficial effects of long-term, regular exercise on cognition and synaptic plasticity. Furthermore, exercise increases the effectiveness of astrocyte-neuron metabolic shuttle by upregulation of astrocytic lactate transporter levels. This review summarizes previous findings related to the neuronal activity-dependent astrocyte-neuron metabolic shuttle. Moreover, we discuss how aging and exercise may shape the astrocyte-neuron metabolic shuttle in cognition-associated brain areas.